pengembangan E-Modul kimia berbasis Problem Based learning untuk meningkatkan literasi sains pada materi hidrolisis garam kelas XI SMA/MA - Fadila Gusman; Indang Dewata; Andromeda Andromeda; Rahadian Zainul (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to develop an e-module based on problem-based learning to improve scientific literacy for class XI Senior High School students. The method used is the 4-D Model development method with the stages of Defining Design, Development and Dissemination. The limitation of this research is only until the third stage. This development assessment is valid and practical. The elements that are validated are content, presentation, language and graphic components. Elements of practice can be seen from the questionnaire conducted by 36 students and 3 teachers. The results of this study are e-modules that meet valid and practical criteria, so that they can be used for salt hydrolysis learning in class XI Senior High School students.